Serum Uric Acid and Left Ventricular Mass in Essential Hypertension - Visco, Valeria; Pascale, Antonietta Valeria; Virtuoso, Nicola; Mongiello, Felice; Cinque, Federico; Gioia, Renato; Finelli, Rosa; Mazzeo, Pietro; Manzi, Maria Virginia; Morisco, Carmine; Rozza, Francesco; Izzo, Raffaele; et al. (Frontiers in Cardiovascular Medicine, 2020)
Serum uric acid (sUA) has been associated with cardiovascular risk. Although the recent mechanistic hypothesis poses the basis for the association between sUA and left ventricular mass index (LVMi), the issue remains poorly investigated in a clinical setup. Through a retrospective analysis of the database of the departmental Hypertension Clinic of University Hospital of Salerno Medical School, we identified 177 essential hypertensives (age 60.3±13.3 years; 85 men), free from uric acid-modulating medications and severe chronic kidney disease, and whose sUA values, anthropometric, clinical and echocardiographic data were available. In the studied cohort, the average duration of hypertension was 8.4±7.1 years. LVMi associated with classical determinants such as age, blood pressure, and kidney function, although after multivariate correction, only age remained significant. Also, sUA correlated positively with LVMi, as well as with body size, metabolism, and kidney function. In a multivariate analysis, sUA confirmed the independent association with LVMi. Also, levels of sUA >5.6 mg/dl associate with larger cardiac size. We confirmed our data in a replicate analysis performed in a larger population (1379 hypertensives) from an independent clinic. Our results demonstrate that sUA increases with LVMi and a cut-off of 5.6 mg/dl predicts larger LV sizes. Our data suggest that hyperuricemia might help to stratify the risk of larger cardiac size in hypertensives